2019
DOI: 10.1002/ajmg.a.61401
|View full text |Cite
|
Sign up to set email alerts
|

IRF2BPL gene variants: One new case

Abstract: To the Editor, Since the first association of pathogenic variants in IRF2BPL (interferon regulatory factor 2 binding protein like) gene with a neurological syndrome in 2018, with the crucial distinction between nonsense (leading to severe neurodevelopmental regression, hypotonia, progressive ataxia, lack of coordination, and epilepsy) and missense variants (with milder phenotype featuring developmental delay and epilepsy) (Marcogliese et al., 2018), there has been further delineation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…In 2018, Tran et al described 11 patients with IRF2BPL de novo truncating variants who were diagnosed with developmental epileptic encephalopathy [1]. In addition to this report, seven other studies found that IRF2BPL gene mutations were responsible for neurodevelopmental disorders [2][3][4][5][6][7][8]. To date, a total of 25 patients with IFR2BPL mutations have been reported worldwide, including in this study.…”
Section: Literature Reviewsupporting
confidence: 53%
See 1 more Smart Citation
“…In 2018, Tran et al described 11 patients with IRF2BPL de novo truncating variants who were diagnosed with developmental epileptic encephalopathy [1]. In addition to this report, seven other studies found that IRF2BPL gene mutations were responsible for neurodevelopmental disorders [2][3][4][5][6][7][8]. To date, a total of 25 patients with IFR2BPL mutations have been reported worldwide, including in this study.…”
Section: Literature Reviewsupporting
confidence: 53%
“…Many studies have recently found that the interferon regulatory factor 2 binding protein-like (IRF2BPL, MIM: 611720) gene with de novo truncating mutations is responsible for neurodevelopmental disorders [1][2][3][4][5][6][7][8]. Additionally, the mutations in IRF2BPL cause variable neurological phenotypes, such as neurodevelopmental regression, cerebellar ataxia, loss of motor skills, and intractable epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, all individuals with a combination of neurological symptomatology and keratoconus or other ophthalmological abnormalities and IRF2BPL variants carried de novo truncating variants (Fig. 1), and it has been noted previously that more severe phenotypes were seen in patients with truncating IRF2BPL variants than in those carrying missense variants [6,11]. The remaining reports of patients with this disease do not mention ophthalmological disease except eye movement abnormalities, but severe neurological symptomatology might have overshadowed eye disease.…”
mentioning
confidence: 79%
“…This leads to agedependent phenotypes in flies that are reminiscent of the progressive phenotypes observed in patients with truncations of IRF2BPL. Individuals with NEDAMSS often progress in development as expected for their age, and the onset of symptoms usually does not occur until the mean age of 5, with some cases only developing disease signs in adolescence (1,2,(36)(37)(38)(39)(40)(41)(42)(43)(44). Decline in motor skills continues until patients become fully dependent of caretakers.…”
Section: Discussionmentioning
confidence: 99%